Penerapan Flipbook Detektif Informasi Berbasis PBL Upaya Peningkatan Sikap Kritis dan Kemampuan Menyimak Kelas Rendah - Caprino, Lovia Heca; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Although listening skills and critical thinking dispositions are foundational to the development of twenty-first-century literacy in primary education, studies that specifically integrate Problem-Based Learning (PBL) with interactive digital media to simultaneously enhance both competencies in lower-grade students remain limited. This study aims to examine the implementation of the PBL model supported by the Information Detective Flipbook (Flipbook Detektif Informasi) and to evaluate its effectiveness in improving critical attitudes and listening skills in Grade III elementary school students. The study employs a mixed-methods approach with an embedded concurrent design, involving 20 Grade III students at SDN Wonoplembon 02 Semarang selected through saturated sampling. Data were collected using structured observation sheets, semi-structured interview guides, field notes, documentation, and pretest–posttest instruments, and analyzed through thematic analysis and the N-Gain statistical test. The results show that the implementation of PBL was effective, with almost all students displaying high curiosity and the ability to evaluate information logically. The average listening score increased from 65.4 to 85.2, with an N-Gain of 0.57 (medium category), and the percentage of mastery rose from 40% to 100%. These findings strengthen the development of constructivist learning theory by demonstrating that PBL can integrate the development of multiple skills in lower-grade students. The study underscores the importance of combining structured instructional models, authentic content in the form of public announcements, and interactive flipbook media to foster active learning and critical inquiry, and it offers practical implications for teachers, curriculum developers, and researchers seeking to integrate digital media with problem-based approaches, including long-term exploration and the examination of moderating factors such as learning styles and student motivation.